Washington Irving and Islam : critical essays - Jalalzai, Zubeda, 1968- (Lexington Books, 2018)
This book examines Washington Irving's biography of the Prophet Muhammed and his other writings that engage Islamic history and the Muslim world. It explores the influence of Spain, Muslim and Christian legends, gender, and heroic biographies on Irving's writing and illustrates Irving's articulation of Orientalism and American nationalism.